“Empirical Research into the Work Motivators of Junior Doctors in the UK Medical Profession at a leading Hospital Trust” - Hill, Matthew (2011)
It is suggested that the management topic of work motivation, with the emphasis on motivation influencing work behaviour and actions, has the potential to help Health care organisations become more efficient. Yet little is known about the work motivators of Junior Doctors who are at the front line of health care, contribute to a Hospitals trusts overall performance, and are the future Consultants in a Hospital. This exploratory research presents a qualitative research account into the work motivation of Junior Doctors, unique in its use of a broad range of motivational factors, in one UK NHS Hospital trust. The research locates the work motivation of Junior Doctors within wider debates of classical work motivation theory, Herzberg’s (1959) two dimensional-need-system, and motivation in the medical profession. Two complementary approaches to data collection were used, a focus group in the prelimary study, and in-depth semi-structured interview’s in the main study to identity the motivating factors for Junior Doctors. A critical incident technique was significantly applied to understand the current motivation of 10 Junior Doctors in the main study. Drawing on the management in practice perspective the study is attentive to the past and current work motivators of Junior Doctors and how they are situated in relation to the ethical, identity, and normative commitments medicine predetermines Doctors in training too. Also the role of prosocial motivation and employee retention was also investigated which produce implications for management. Specifically it was found that the possibility of growth, level and quality of clinical supervision, and nature of the work itself currently motivated Junior Doctors, which in the past were motivated by working conditions. These motivators for Junior Doctors differed between medical specialities, are factors which contribute to self-identity, and it was indicated that extrinsic and intrinsic motivators would influence a Junior Doctors motivation to stay at the Hospital trust. The research highlights the need to further comprehend what motivates Junior Doctors and for more empirical research into the wider managerial issues of managing Doctors in training.